A Narrow Groove Structure Based Plasmonic Refractive Index Sensor - Yanjun Hu; Yulong Hou; Abdul Ghaffar; Wenyi Liu (IEEE Access, 2020)
A refractive index (RI) sensor based on plastic optical fiber (POF) with narrow groove structures coated with a gold layer (POF-NGS (Au)) is proposed and demonstrated. The proposed sensor was characterized using intensity interrogation, where the change in transmission power is induced by light filed interaction and Surface Plasmon Resonance (SPR). Narrow groove structures with lengths of 5 mm were fabricated using an ultraviolet laser, and a gold layer was sputtered to the surface of the whole fiber. The effect of the machining pitch on the RI response was studied. In this paper, dB and $μ \text{W}$ were used to represent the change of transmission power. Experiments have shown that the POF-NGS (Au) RI sensor has liner response between 1.340 and 1.356. The curvature of the output is largest when the machining pitch is $400~μ \text{m}$ with sensitivity 12.5 dB/RIU ($126~μ \text{W}$ /RIU). The repeatability and temperature sensitivity characteristics were also characterized. Furthermore, the proposed sensor offers improved stability and signal to noise ratio.